TRANSFORMING OF POULTRY MANURE INTO VALUE: COMMERCIAL STRATEGIES FOR COMPOSTING, BIOENERGY AND ANIMAL NUTRITION - Mojarla Raghavendar (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Poultry manure is generated in large quantities by the rapidly expanding poultry industry and poses serious environmental management challenges when disposed of without appropriate treatment. This review critically synthesizes commercial technologies  for  the  valorization  of  poultry  manure  into  compost,  bio  energy  and value-added agricultural inputs, with emphasis on process performance, safety and applicability  under  Indian  conditions. Aerobic  composting  (windrow,  in-vessel  and vermin  composting),  anaerobic  digestion  and  thermo  chemical  conversion  routes are comparatively evaluated based on operating parameters, pathogen reduction efficiency,  nutrient  conservation  and  scalability.  Anaerobic  digestion  offers  dual benefits of renewable biogas generation and nutrient-rich digestate production, while composting remains the most economically feasible option for decentralized farm- level manure management. Pyrolysis-derived biochar and bio-oil provide emerging opportunities for carbon sequestration and renewable fuel production, though economic and infrastructural barriers currently limit their adoption in India. The utilization of processed poultry manure in animal feed is constrained by regulatory and biosafety considerations. This review highlights major technological gaps, economic challenges and policy needs for sustainable poultry manure valorization and proposes integrated circular-economy   frameworks   suitable   for   Indian   poultry   production   systems.